Distinct Physiological Roles of Three Phospholipid:Diacylglycerol Acyltransferase Genes in Olive Fruit with Respect to Oil Accumulation and the Response to Abiotic Stress - Hernández, M. Luisa; Moretti, Samuele; Sicardo, M. Dolores; García, Úrsula; Pérez, Ana; Sebastiani, Luca; Martínez-Rivas, José M. (Frontiers in Plant Science, 2021)
Three different cDNA sequences, designated OepPDAT1-1, OepPDAT1-2, and OepPDAT2, encoding three phospholipid:diacylglycerol acyltransferases (PDAT) have been isolated from olive (Olea europaea cv. Picual). Sequence analysis showed the distinctive features typical of the PDAT family and together with phylogenetic analysis indicated that they encode phospholipid:diacylglycerol acyltransferases. Gene expression analysis in different olive tissues showed that transcript levels of these three PDAT genes are spatially and temporally regulated and suggested that, in addition to acyl-CoA:diacylglycerol acyltransferase, OePDAT1-1 may contribute to the biosynthesis of triacylglycerols in the seed, whereas OePDAT1-2 could be involved in the triacylglycerols content in the mesocarp and, therefore, in the olive oil. The relative contribution of PDAT and acyl-CoA:diacylglycerol acyltransferase enzymes to the triacylglycerols content in olive appears to be tissue-dependent. Furthermore, water regime, temperature, light, and wounding regulate PDAT genes at transcriptional level in the olive fruit mesocarp, indicating that PDAT could be involved in the response to abiotic stresses. Altogether, this study represents an advance in our knowledge on the regulation of oil accumulation in oil fruit.